AB0349 Significance of Positive Anti-Ccp Antibody and Development of Interstitial Lung Disease in Patients with and without Clinically Apparent Rheumatoid Arthritis. (10th June 2014) - Imran, M.; O'Brien, S.; Hamblin, M.; Maz, M.
Abstract : Background: Checking of CCP antibodies and rheumatoid factor are often a component of evaluation of patients with ILD 1, 2 . Objectives: Determine the significance of RA related autoantibodies in patients who develop ILD, whether or not they meet the diagnostic criteria for RA, supporting the hypothesis that RA related autoimmunity could be initiated in non-articular sites, such as the lung. Methods: Retrospective chart review of 160 subjects with ILD to identify cases with ILD, RA related autoantibody positivity (anti CCP) and no clinical evidence of articular RA. Patients who were evaluated at the University of Kansas Medical Center Pulmonary and Rheumatology clinics, between January 2008 to November 2013 were included in the study. Each subject had serologic testing, pulmonary function testing and thoracic computed tomography scan as part of routine clinical evaluation. Results: Fifty five patients who had ILD along with positive RF or anti-CCP were identified. Out of those fifty five patients, only four patients with ILD and anti-CCP positivity (median 94.7, range 36-138) and no articular findings of RA were identified. Three patients were male with a mean age of 65 at the time of diagnosis of ILD. Only one male had a history of smoking. The female patient was a 53 year old cocaine abuser who also had a p-ANCA titer at 1:1280, MPO >8, and PR3 (0.4), which were positive due to adulterated cocaine use and not due to vasculitis. One patient died within 6 years of diagnosis of ILD and never developed articular symptoms consistent with RA; the remaining three patients continue to follow in Pulmonary and Rheumatology clinics and have not developed RA related articular symptoms yet. An additional 9 patients with a positive RF and negative anti-CCP with ILD and no articular findings of RA were also identified. Majority of these patients were female, and most were former cigarette smokers. However, 6 of these 9 were also noted to be seropositive for another auto-antibody ( ANA>1:640). Among patients with ILD and articular symptoms consistent with a clinical diagnosis of rheumatoid arthritis, a positive anti-CCP antibody (28 patients) had a strong association with ILD (x 2 =8.526, p=0.0035). Of those patients with pulmonary function testing performed, 73% (30 of 41) already had moderate to severe restrictive lung disease or a severe impairment in diffusing capacity at the time of initial pulmonary evaluation. Conclusions: These findings suggest that majority of patients with ILD and positive RF and/or anti CCP antibodies were diagnosed with or met the diagnostic criteria for RA. Consistent with other reports, there was a strong association with anti-CCP positivity and the presence of interstitial lung disease. 5 These findings highlight ILD as an extra-articular manifestation of rheumatoid arthritis, and suggest that a positive anti-CCP antibody might identify a population of RA patients who should undergo routine screening and surveillance for early detection and management of ILD. Further investigation and prospective studies are needed to fully assess the implications of a positive anti-CCP and RF in patients with ILD but not articular RA. References: Lamblin C, et. al, EurRespir J Suppl. 2001;32:69s–80s Gizinski AM, et. at, ClinRheumatol.2009;28(5):611–3 Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.2620